Fungal outbreak in the Catacombs of SS. Marcellino and Pietro Rome (Italy): From diagnosis to an emergency treatment - De Leo, Filomena; Dominguez-Moñino, Irene; Jurado, Valme; Bruno, Laura; Saiz-Jimenez, Cesareo; Urzì, Clara (Frontiers in Microbiology, 2022)
The present study reports a sudden fungal outbreak occurred in the corridor near the entrance of the Catacombs of SS. Marcellino and Pietro in Rome (Italy) observed after one year of a restoration treatment that interested the walls of the entrance of the Catacombs and some artifacts placed in situ. The colonization was observed on the vault at the entrance and in correspondence of the restored marble pieces displayed on the left side of the corridor. No growth was observed in the right side where similarly treated marbles slabs were placed. Samples taken in correspondence of fungal biofilm were analyzed through the combined use of microscopical, cultural and molecular tools and showed that the vault and the left side of the corridor entrance were colonized by a complex fungal biofilm consisting mainly of Coniophora sp. and other genera, such as Hypomyces, Purpureocillium, Acremonium, Penicillium and Alternaria, many of which are well known as responsible of biodeterioration of stone surfaces. Regarding the brown-rot basidiomycete Coniophora, it was able to form very large colonies on the substrata with a diameter up to 57 cm. Although the direct observation under light microscope clearly evidenced the presence of abundant brown fungal conidia, several attempts to cultivate the microorganism failed, therefore only through DNA sequencing analyses it was possible to identify and characterize this fungus. There is very little literature on the genus Coniophora that is reported as one of the causes of wet-rot decay of wood in buildings. A connection with calcium containing materials such as bricks and mortars was demonstrated, but no data were available about a possible role of this species in the biodeterioration of stones. This study features the first finding of a strain related to the basidiomycetous genus of Coniophora in the order Boletales in association with evident phenomena of biodeterioration.